The Sustainability of Health-Based Projects: An Integrative Literature Review - Sah, Muskan; Kumari, Rani; Prajapati, Aayushman; Pravin, Nusarat; Poudel, Sandip (Madhesh Journal of Interdisciplinary Research, 2026)
Sustainability of health-based projects (HBPs) is a persistent challenge in both developing and developed health systems, particularly where donor dependence and resource constraints limit long-term continuity. This study presents a structured literature review aimed at identifying and synthesizing key factors influencing the sustainability of HBPs. The review draws on theoretical and empirical literature from sustainability science, health systems research, and project management to develop an integrated understanding of sustainability determinants. Findings reveal that sustainability is multidimensional and shaped by interrelated social, financial, organizational, and institutional factors. Community involvement strengthens ownership, participation, and local capacity, thereby enhancing project continuity. Service charges contribute to financial sustainability but may raise equity concerns in access to care. Customer care improves trust, satisfaction, and utilization of services, while diversified financial resources enhance resilience and reduce dependence on external funding. The study concludes that sustainability of HBPs requires an integrated and context-sensitive approach that balances financial viability, social inclusion, and institutional embedding. The review contributes to theory by consolidating fragmented literature and proposing a conceptual framework for understanding sustainability of NGO-led health interventions, particularly in developing country contexts.